Nanoparticle Delivery of Artesunate Enhances the Anti-tumor Efficiency by Activating Mitochondria-Mediated Cell Apoptosis - Liu, Rui; Yu, Xiwei; Su, Chang; Shi, Yijie; Zhao, Liang (Nanoscale research letters, 2017)
Artemisinin and its derivatives were considered to exert a broad spectrum of anti-cancer activities, and they induced significant anti-cancer effects in tumor cells. Artemisinin and its derivatives could be absorbed quickly, and they were widely distributed, selectively killing tumor cells. Since low concentrations of artesunate primarily depended on oncosis to induce cell death in tumor cells, its anti-tumor effects were undesirable and limited. To obtain better anti-tumor effects, in this study, we took advantage of a new nanotechnology to design novel artesunate-loaded bovine serum albumin nanoparticles to achieve the mitochondrial accumulation of artesunate and induce mitochondrial-mediated apoptosis. The results showed that when compared with free artesunate’s reliance on oncotic death, artesunate-loaded bovine serum albumin nanoparticles showed higher cytotoxicity and their significant apoptotic effects were induced through the distribution of artesunate in the mitochondria. This finding indicated that artesunate-loaded bovine serum albumin nanoparticles damaged the mitochondrial integrity and activated mitochondrial-mediated cell apoptosis by upregulating apoptosis-related proteins and facilitating the rapid release of cytochrome C.